A Secret Society History of the Civil War - Lause, Mark A. (Book collections on Project MUSE., 2011)
This unique history of the Civil War considers the impact of nineteenth-century American secret societies on the path to as well as the course of the war. Beginning with the European secret societies that laid the groundwork for Freemasonry in the United States, Mark A. Lause analyzes how the Old World's traditions influenced various underground groups and movements in America, particularly George Lippard's Brotherhood of the Union, an American attempt to replicate the political secret societies that influenced the European revolutions of 1848. Lause traces the Brotherhood's various manifestations, the most conspicuous being the Knights of the Golden Circle (out of which developed the Ku Klux Klan), and the Confederate secret groups through which John Wilkes Booth and others attempted to undermine the Union. Lause profiles the key leaders of these organizations, with special focus on George Lippard, Hugh Forbes, and George Washington Lafayette Bickley._x000B__x000B_Antebellum secret societies ranged politically from those with progressive or even revolutionary agendas to those that pursued conservative or oppressive goals. This book shows how, in the years leading up to the Civil War, these clandestine organizations exacerbated existing sectional tensions in the United States. Lause's research indicates that the pervasive influence of secret societies may have played a part in key events such as the Freesoil movement, the beginning of the Republican party, John Brown's raid on Harpers Ferry, Lincoln's election, and the Southern secession process of 1860-1861._x000B__x000B_This exceptional study encompasses both white and African American secret society involvement, revealing the black fraternal experience in antebellum America as well as the clandestine operations that provided assistance to escaped slaves via the Underground Railroad. Unraveling these pervasive and extensive networks of power and influence, A Secret Society History of the Civil War demonstrates that antebellum secret societies played a greater role in affecting Civil War-era politics than has been previously acknowledged.